PERAN NASYIATUL AISYIYAH DALAM WACANA GENDER DAN PENDIDIKAN PROFETIK BAGI PEREMPUAN DI BIMA - Umar Umar; Husnatul Mahmudah; Mei Indra Jayanti (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Nasyiatul Aisyiyah is a pioneering organization of the women's movement that is concerned with developing the creativity of Muslim women so that they are able to play an important role in Islamic social activities. This research aims to describe the role of Nasyiatul Aisyiyah in gender discourse and prophetic education for women in Bima. This type of research is qualitative descriptive research. The source of research data focused on female figures and leaders of the organization of Nasyiatul Aisyiyah in Bima area. The results showed that there are several forms of the role of Nasyiatul Aisyiyah in gender discourse and profectic education for women in Bima, among others; Nasyiatul Aisyiyah was instrumental in the prevention of violence in women through campaign activities and socialization of violent prevention of twigs, Nasyiatul Aisyiyah instrumental in encouraging the lack of active participation of women in the realm of domesetik and pulblik especially in the aspect of power relationship, and Nasyiatul Aisyiyah in the role of prophetic education conducted through the program of da'wah women in each branch and branches of Nasyiatul Aisyiyah in Bima area.